Driving Digital Transformation with Robotic Process Automation - Vaibhav Lomte; Krishna T. Madrewar (International Journal of Advanced Robotics and Automation Technology, 2023)
Compared to conventional administration methods, robotic process automation (RPA) has a number of advantages. Without a less intrusive mechanical hurdle, it allows for cost savings and resource liberation. Other benefits include more output, greater precision (and fewer errors), the potential to streamline regulatory compliance, quicker service (and hence higher customer satisfaction), and more uniformity. A description of business and digital transformation using procedure technology.The creation and use of computer-generated robots using algorithms to carry out repetitive, rule-based tasks now carried out by people in workflow and process-related applications (typically legacy systems) and functions is known as robotic process automation (RPA). Robotic process automation (RPA) refers to the programmer itself that automates methods as well as the method (or process) of identifying the procedures and duties that are most appropriate for RPA. It also refers to the method's strategic plan for achieving successful design and application of the RPA pattern, macros, along with computations.
Keywords: Automation; RPA; Robotics; artificial intelligence; software